FACTORS AFFECTING STUDENTS’ STUDY TIME MANAGEMENT OF CLASS B SEMESTER V OF ENGLISH EDUCATION STUDY PROGRAM AT UNIVERSITY OF NIAS - Adieli Laoli; Yulidartini Larosa; Nurmawati Harefa; Ica Murni Tafonao (J-Shelves of Indragiri (JSI), 2025)
Effective study time management is crucial for academic success, particularly for students who must balance coursework, assignments, and extracurricular activities. However, many students struggle with managing their time efficiently, leading to increased stress and lower academic performance. This study aims to analyze the factors influencing study time management among Semester V Class B students of the English Education Study Program at the University of Nias. Using a qualitative approach with a descriptive-analytical method, this research explores factors affecting students’ ability to organize and manage their study time effectively. The findings indicate that motivation and self-discipline are the dominant factors, while the learning environment and support from lecturers and peers serve as significant influences. Additionally, challenges such as technological distractions, heavy academic loads, and extracurricular commitments hinder students' time management. To address these issues, students commonly use scheduling and prioritization techniques. The study concludes that universities should provide targeted guidance and training on effective time management strategies to enhance students’ academic performance and overall well-being.